A Time-Domain Active Vibration Control Algorithm for Helicopter Based on a Prior Error Channel Identification Strategy. (3rd January 2018) - Lu, Yang; Feng, Jianbo
Abstract : During the flight tests of Z-11 helicopter, the previous method for active vibration control of helicopter suffered from the problems of slow convergence speed and big residual vibration. In order to mitigate these problems, a new method was proposed on the basis of the previous one. Here, a new error channel modeling method is used, which is named the prior error channel identification strategy. And the active control process and the error channel identification process are simplified to improve performance of the system. Besides, the complexity of the method is reduced. Active vibration control simulations were performed based on a simplified model of helicopter fuselage. The simulation results show that the proposed method has lower residual vibration, faster convergence speed, and better capacity for resisting disturbance compared with the previous method. Finally, an active control of structure response experiment was conducted on a free-free beam, and good inhibitory effect of the vibration response of the free-free beam was obtained. The results illustrate that the proposed method based on the prior error channel identification strategy is effective.